2005
DOI: 10.4326/jjcvs.34.237
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Revascularization under Carbon Dioxide Angiography

Abstract: We have long advocated the usefulness, accuracy and safety of carbon dioxide angiogrphy for patients with iodine allergy and renal dysfunction. In addition to its utility, no specialized apparatus is necessary for carbon dioxide angiography. Carbon dioxide as a contrast material has been adopted by consensus for use in endovascular revascularization. Here we report 4 cases of endovascular revascularization using carbon dioxide angiography. Two of the four patients had an iodine allergy, one had renal dysfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…16,17) However, this method is associated with severe complications and poor image quality. 18) Carbon dioxide angiography results in poor imaging of BTK lesions because of gas bubbles. Moreover, patients often experience severe pain that may cause them to move their legs during the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…16,17) However, this method is associated with severe complications and poor image quality. 18) Carbon dioxide angiography results in poor imaging of BTK lesions because of gas bubbles. Moreover, patients often experience severe pain that may cause them to move their legs during the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The safety and efficacy of CO 2 as a satisfactory submucosal injection agent during ESD have been demonstrated. Shikata H et al [22] performed endovascular revascularization under CO 2 gas angiography for patients with iodine allergy and renal dysfunction and found no direct or indirect complications of CO 2 gas angiography after injecting up to 200 ml of CO 2 gas. Consequently, we think that the infusion of CO 2 gas into the preperitoneal space does not cause any clinical problems unless a very large volume of CO 2 gas, probably over 200 ml, is injected directly into blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cardi et al reported side effects in seven of 1,200 cases of CO2 angiogra-phy (19). In order to prevent adverse effects, the total amount of CO2 on angiography should be limited to less than 200 mL, with an upper limit for the rate of application of 25 mL/s (20).…”
Section: Discussionmentioning
confidence: 99%